Behind Your Walls - Zwartjes, Frans (The Netherlands, 1970)
The film director's two visions of womanhood in "Behind Your Walls" have all the febrile frustration associated with his previous work. Flesh looks like crisp paper about to be despoiled, a torpid heat reduces movement to fidgets and hesitations.
Silent
Verzio Film Festival Submission
Keywords: Experimental films